Energy Monitoring and Control of Automatic Transfer Switch between Grid and Solar Panel for Home System - Joko Slamet Saputro; Hari Maghfiroh; Feri Adriyanto; Muhammad Renaldy Darmawan; Muhammad Hamka Ibrahim; Subuh Pramono (Association for Scientific Computing Electronics and Engineering (ASCEE), 2023)
In this digital age, most aspects of life require an electric supply. The availability of electrical power is very critical to maintaining the continuity of the system in various applications. To maintain system continuity, the Energy Monitoring and Control of an Automatic Transfer Switch (ATS) between the Grid and Solar Panel is proposed. The system consists of an Automatic Transfer Switch, Home Solar Power Plant, and Automatic Charging. The function of the monitoring system is to monitor the voltage, current, and power across the device, the operation mode of the ATS, and the State of Charge (SoC) of the battery. The control system is to control the operation mode of ATS according to the energy source selected by the user on the Internet of Things (IoT) interface. The results show that the system can successfully monitor solar panel conditions, AC output, and battery's State of Charge through Blynk IoT. The ATS works automatically with a switching delay of 20ms to 26ms, while on the user's command, the average switching delay is 303.33ms to activate the relay and 185ms to deactivate the relay.